PASAR SAHAM INDONESIA DALAM PERSPEKTIF MAKROEKONOMI - Septya Magisa, Nurul (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STIE Pontianak, 2023)
The stock market is an investment place that has the potential to provide large profits, but also has high risks. In Indonesia, the IHSG (Composite Stock Price Index) is used as a benchmark for stock market performance. Profitable and low-risk stock investments require attention to macroeconomic factors at both the national and global levels. These factors include inflation, BI rate, exchange rate (USD/IDR), and Brent oil price. This research aims to identify the influence of various macroeconomic factors on the IHSG. The method used in this research is the ARDL-ECM model. The research results show that in the short term, inflation, BI rate, exchange rate (USD/IDR), and Brent oil prices have a significant effect on the IHSG. However, in the long term, only inflation does not have a significant influence on the IHSG.